Analysis of spatial effects and influencing factors of rural industrial integration in China - Yuan Fang; Ying Yang (Scientific Reports)
Abstract The integrated development of rural industry is an important path to accelerate rural revitalization, promote modernization of agriculture and rural areas, and build a strong agricultural country. Based on the evaluation index system of rural industrial integration, the level of rural industrial integration of 31 provinces (municipalities and autonomous regions) in China is measured from 2012 to 2022; ArcGIS, exploratory spatial data analysis method, and Tobit model are used to classify the level of rural industrial integration, explore the spatial distribution characteristics, and analyse the influencing factors, respectively. The results show that: (1) Rural industrial integration indicator scores show an increasing trend. (2) The level of rural industrial integration varies greatly from region to region, generally showing the development trend of eastern region > central region > western region. (3) The comprehensive level of rural industrial integration and other subsystems in general show significant polarised agglomeration. (4) There is regional heterogeneity in the impact of different factors on rural industrial integration. In view of this, it is recommended to improve the benefit linkage mechanism, give full play to the regional characteristics and advantageous resources of each region, and strengthen inter-regional exchanges and cooperation.